Geometric Relations of the Formation of a Cut Surface - Karol Vasilko; Anna Macurova (Communications - Scientific letters of the University of Zilina, 2002)
When assessing the roughness of the cut surface a simplified relationship is used representing the dependency of maximum deviation of a roughness and a representing feed in the form Rz 8 f r 2  , where Rz is the roughness of the cut surface, f is a feed and r is a radius of the curving of the knife. The latest approaches illustrate the inaccuracy of this dependency. On the basis of the experimental measurements the authors analyse new relationships between cutting conditions and roughness of the cut surface. These enable to predict morfology of the cut surface to the accession of the semi-product in the production facilities and to select optimal cut conditions of the aspect of the required quality of the surface.